The surgical treatment of talocrural luxation in nine cats - Schmökel, H. G.; Ehrismann, G. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The surgical treatment of talocrural luxation in nine cats was evaluated. Stabilisation of the joint was achieved by internal fixation of fractures and ligament replacement. A splint provided external support in eight cats and an external fixator was used in one. The support remained in place for three to seven weeks in five cats (group #1) but is was removed after ten days in four (group #2) and physiotherapy applied to the leg. Using a scoring system the repairs were assessed at 5-30 months, when cats in group #2 had better function and less DJD than those in group #1. Early mobilisation and weight-bearing may have favourably influenced this result.The treatment of talocrural luxations in cats is reported. Early physiotherapy and mobilisation appeared to benefit the outcome.
Keywords: Tarsal luxation; early mobilisation; cat